Mechanical properties of carbon fiber reinforced with carbon nanotubes and graphene filled epoxy composites: experimental and numerical investigations - P Phani Prasanthi; M S R Niranjan Kumar; M Somaiah Chowdary; V V Venu Madhav; Kuldeep K Saxena; Kahtan A Mohammed; Muhammad Ijaz Khan; Gaurav Upadhyay; Sayed M Eldin (Materials Research Express, 2023)
The mechanical properties of carbon fiber-reinforced epoxy composites were identified by adding carbon-based nano-reinforcements, such as multi-wall carbon nanotubes (CNTs) and graphene platelets (GP), into the epoxy matrix by conducting suitable experiments. The main focus of this study is to compare the tensile modulus, tensile strength, flexural modulus, flexural strength, and thermal conductivity of carbon fiber-reinforced epoxy composites with nanoparticle reinforcement. The results revealed that adding CNTs and GP nanoparticles improved the mechanical properties compared to a pure carbon fiber-reinforced plastic composite. However, compared to CNTs, the GP’s addition has increased the mechanical properties of the CFRP composite. In addition, scanning electron microscopy (SEM) images were presented to explore the microstructural characterization of carbon fiber-reinforced nanoparticle-reinforced composites. Further, using numerical studies, the transverse modulus, major and minor Poisson’s ratio of the carbon fibre reinforced with CNT and GP particle reinforcement were estimated. The current study is applied to the efficient design of nanoparticle reinforced carbon fibre reinforced composites.